2012
DOI: 10.1021/ie300163v
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Sulfite Oxidation in the Magnesium-Based Wet Flue Gas Desulfurization Process

Abstract: The kinetics of sulfite oxidation in the magnesium-based wet flue gas desulfurization (FGD) process were investigated in a stirred bubbling reactor by varying the concentrations of MgSO 3 and MgSO 4 , pH, air flow and temperature. The reaction was found to be 0.88 order with respect to magnesium sulfite and the oxidation could reach the maximum rate when the pH value was close to 6.5. The mechanism of the oxidation was discussed, and it was concluded that the oxidation is controlled by diffusion of oxygen. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 30 publications
3
36
0
Order By: Relevance
“…Figure 7 showed that when the pH was increased from 5.0 to 7.0, the constant increase in the oxidation capability of dissolved oxygen engendered an increase in the oxidation rate. This phenomenon is consistent with the results reported by Shen [3]. When the pH was increased from 7.0 to 9.0, the constantly increasing OH 2 could easily combine with the transition metal Co on the surface of the catalyst, covering active sites and inducing catalyst deactivation; this led to a continuous drop in the oxidation rate of magnesium sulfite.…”
Section: Kinetics Of Catalytic Oxidation Of Magnesium Sulfitesupporting
confidence: 92%
“…Figure 7 showed that when the pH was increased from 5.0 to 7.0, the constant increase in the oxidation capability of dissolved oxygen engendered an increase in the oxidation rate. This phenomenon is consistent with the results reported by Shen [3]. When the pH was increased from 7.0 to 9.0, the constantly increasing OH 2 could easily combine with the transition metal Co on the surface of the catalyst, covering active sites and inducing catalyst deactivation; this led to a continuous drop in the oxidation rate of magnesium sulfite.…”
Section: Kinetics Of Catalytic Oxidation Of Magnesium Sulfitesupporting
confidence: 92%
“…AISI 1010) contains a significant amount of Mn, which can be corroded into Mn 2+ ion. This ion has a catalytic oxidation effect on sulfite [38]. The catalytic oxidation rate of sulfite is generally expressed as [39],…”
Section: Water Film Region Equationsmentioning
confidence: 99%
“…However, MgO flue gas desulfurization features high desulfurization efficiency, low energy consumption, less investment requirement, and reliable operation; thus, it satisfies the ultra-low emission requirements of industrial boilers under fluctuating flue gas conditions. Moreover, magnesium sulfate, which is obtained as the desulfurization product, can be used as an industrial raw material or agricultural fertilizer and has a high economic value [5][6][7]. To prevent the crystallization of magnesium sulfate in the absorption tower in a traditional magnesia desulfurization process, the concentration of magnesium sulfate in the desulfurization solution should be controlled below 10%.…”
Section: Introductionmentioning
confidence: 99%